Violence and Warfare: A Critical Assessment of the Just War Tradition in a Rebalancing World - OGUNBANJO, Bimbo (Al-Adab Journal, 2025)
The Just War tradition (JWT) is viewed in this paper as a corpus of ideas that discusses the morality and ethics of war. It has changed throughout more than 1,500 years, making it a complicated one. The Just War tradition is broad and multifaceted, yet it is confined within some essential principles that determine its boundaries. It differs from pacifism in that it holds that wars can occasionally be justified and from realism, which views war as outside the purview of moral judgment, in that it holds that both the choice to go to war and the tactics used in conducting it are subject to moral inspection. Within such confines, just war theorists disagree with one another not only about subtleties of the theory but also over fundamental issues like whether or not a war may be justified by something other than the necessity of defending oneself against an already-initiated armed attack. This paper’s main goal is to provide a clear and comprehensive understanding of the JWT, the conditions under which it permits and restricts acceptable damages and the moral conundrums these arguments raise. Regarding modern just war theory, one of the central concerns is whether war can be fought and damage done for "humanitarian" or "cosmopolitan" purposes, including protecting human rights. Stated differently, the question is whether there exists a clear and present need to conduct war. This paper lays out the main problems with the use of violence, evaluates the cosmopolitan and anti-cosmopolitan contributions to Just War thinking, and ends with some observations on the suitability of Just War thinking and its connection to cosmopolitanism.